Urgensi Menggali Potensi Pendapatan Daerah Selain PBB Untuk Kesejahteraan, Meningkatkan Hak Ekonomi Masyarakat dan Peka HAM - Abdul Azis; Merah Johansyah; Bayu Mandiri; Stefano Stefano; Hasriyani Hasriyani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Local Own-Source Revenue (PAD) serves as a vital instrument in supporting regional independence and public welfare. For decades, the Land and Building Tax (PBB) has been one of the primary sources of local revenue; however, excessive dependence on PBB is considered less effective in promoting equitable economic development and enhancing citizens’ economic rights. Forcing PBB increases of hundreds of percent, as has recently occurred in a number of regions such as Pati Regency, Central Java, and dozens of other regions amid the current difficult economic situation, has invited criticism and protests. This policy has been accused of violating human rights. For this reason this study aims to analyze the urgency of exploring alternative local revenue sources beyond PBB, such as local taxes, public service retributions, management of regional assets, and innovative revenue models based on local potential. The research uses a qualitative approach through literature review and fiscal policy analysis at the regional level. The findings indicate that diversification of local revenue sources can strengthen regional fiscal capacity, improve public service delivery, and foster broader community economic participation. By sustainably and transparently developing local potential, local governments can not only enhance community welfare but also uphold the principle of economic justice as mandated by the Constitution. Therefore, optimizing local revenue sources beyond PBB represents a strategic step toward inclusive and equitable regional economic independence.